Surface functionalization of central venous catheter with mycofabricated silver nanoparticles and its antibiofilm activity on multidrug resistant Acinetobacter baumannii. (January 2020) - Neethu, Sahadevan; Midhun, Sebastian Jose; Radhakrishnan, E.K.; Jyothis, Mathew
Abstract: The mycofabrication of silver nanoparticles (AgNPs) through green chemistry protocol is an advanced methodological progress in medical nanotechnology. Mycofabricated AgNPs are less toxic due to an aura of biomolecules around the nanoparticles. Hence the mycofabricated AgNPs can be used for clinical applications. The present study explores the antibiofilm activity of mycogenerated AgNPs, which were synthesized by the enzymatic reduction of silver nitrate using the marine algicolous endophytic fungus Penicillium polonicum ARA10. The mycogenerated AgNPs showed very specific and potent bactericidal activity against Acinetobacter baumannii . Anti- A.baumannii activities of mycogenerated AgNPs on planktonic as well as biofilm embedded cells were explored. The physical impact of synthesized AgNPs on A.baumannii was investigated by scanning electron microscopy and fluorescence microscopy. A bionanocomposite coating for the central venous catheter (CVC) was formulated using the mycogenerated AgNPs and polydopamine. The bionanocomposite surface was characterized by field emission scanning electron microscopy, water contact angle measurement, and Raman spectroscopy. The results showed that the mycogenerated AgNPs have potent antibiofilm activity on biofilms of A.baumannii . The scanning electron microscopy (SEM) and fluorescence microscopy images showed noticeable aberrations on the ultrastructure of A.baumannii . The SEM and FE-SEM images of biofilms on the surface of CVC samples proved that the AgNPs at minimum bactericidal concentration could destroy the structure of biofilms and lyses the bacterial cell. Thus, the present study establishes a new way to the development of 'antibacterial surfaces' based on mycogenerated AgNPs. Graphical abstract: Image 1 Highlights: Characterization of the synthesized AgNPs. Antibiofilm activity of AgNPs on the planktonic cells of Acinetobacter baumannii . A mild method of surface functionalization of central venous catheter was proposed. Surface characterization of the modified catheter samples demonstrated. Efficacy of AgNPs decorated central venous catheter on the biofilms of Acinetobacter baumannii was explored.